Recommended Musculoskeletal and Sports Medicine Curriculum for Internal Medicine Residency Training. Issue 2 (February 2021) - Liddle, David G.; Changstrom, Bradley; Senter, Carlin; Meirick, Paul; Stern, Nicole; Putukian, Margot; Shah, Selina; Powell, Amy; Dixit, Sameer; Eerkes, Kevin; Moran, Byron; Barnes, Kenneth P.; et al.
Abstract : Abstract: Patients present to primary care physicians with musculoskeletal complaints more often than they do for upper respiratory infections, hypertension, or diabetes. Despite this, instruction in musculoskeletal medicine for internal medicine residents represents less than 1% of their total didactic and clinical education time. We recognize the immense breadth of knowledge and skill required to train residents in the practice of internal medicine. This curriculum guideline defines a recommended training strategy, and supplies relevant resources, to improve musculoskeletal education among internal medicine residents to optimize patient care. This curriculum guideline was created by internists who are sports medicine specialists. Sports medicine physicians promote overall health and well-being while providing expertise in acute and chronic musculoskeletal conditions, as well as how disease affects exercise and using exercise as medicine for people with chronic disease.